2002
DOI: 10.1159/000048315
|View full text |Cite
|
Sign up to set email alerts
|

<i>L</i>-Carnitine in Experimental Retinal Ischemia-Reperfusion Injury

Abstract: The effect of L-carnitine on retinal ischemia-reperfusion injury was evaluated in guinea pigs. 90 min of pressure-induced retinal ischemia followed by 24 h of reperfusion was established in both eyes of 2 groups of animals receiving either L-carnitine (100 mg/kg repeated in 5 doses) or saline intraperitoneally. After enucleation of all the eyes, including those of a control group, malonyldialdehyde (MDA) levels and the thickness of the retinal tissue were measured in 3 groups. The mean MDA value and the tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Alagoz et al (27) examined the efficiency of LC on ischemia-reperfusion injury in guinea pigs. They found that the mean MDA value and the tissue thickness of the LC-treated group were statistically insignificant versus those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Alagoz et al (27) examined the efficiency of LC on ischemia-reperfusion injury in guinea pigs. They found that the mean MDA value and the tissue thickness of the LC-treated group were statistically insignificant versus those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ocular symptoms, a number of reports have been released. One states that there was a reduction in carnitine inside the ocular lens of diabetic rats [ 33 ], while another found carnitine to be effective for ischemic re-reflux disorder in the retina of guinea pigs [ 34 ]. There is also a report of a clinical test with human subjects that showed a supplement containing carnitine to counter macular degeneration [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for oxidation stress markers, lipid peroxides decreased significantly in the Test Group. Carnitine plays an important role in lipid metabolism [ 8 ] and possesses anti-oxidation activity [ 19 , 22 , 34 , 36 ], so a decrease in lipid peroxides is not contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…A previously described pressure induced retinal ischemia was performed in the placebo and drug groups. 16 Accordingly both anterior ocular chambers of each animal of the placebo and drug test groups were cannulated with a 27 gauge needle connected to a bottle of normal saline and the bottle was rapidly lifted to a height of 205 cm in order to raise the intraocular pressure to 150 mmHg and sustained for 90 min Reperfusion was established by lowering the saline bottle to the eye level. The eyes were decanulated and underwent reperfusion for 24 hours.…”
Section: Methodsmentioning
confidence: 99%